2020
DOI: 10.3389/fgene.2019.01386
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Macrophage Chromatin Is Modified to Orchestrate Host Response to Mycobacterium bovis Infection

Abstract: Bovine tuberculosis is caused by infection with Mycobacterium bovis, which can also cause disease in a range of other mammals, including humans. Alveolar macrophages are the key immune effector cells that first encounter M. bovis and how the macrophage epigenome responds to mycobacterial pathogens is currently not well understood. Here, we have used chromatin immunoprecipitation sequencing (ChIP-seq), RNA-seq and miRNA-seq to examine the effect of M. bovis infection on the bovine alveolar macrophage (bAM) epig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 92 publications
(108 reference statements)
0
29
0
Order By: Relevance
“…In this regard, previous work has shown that macrophage PI3K/AKT signalling is key to a range of cellular processes associated with host-pathogen interaction in MTBC infections, including modulation of cell death pathways, manipulation of signalling downstream of TLRs, and initiation of granuloma formation (Maiti et al 2001;A et al 2012;Cho et al 2013;Liu et al 2016;Brace et al 2017;Yang et al 2018). We have also recently demonstrated that genes encoding protein products embedded in the PI3K/AKT pathway are primary targets for chromatin modifications that substantially alter bAM gene expression in response to M. bovis infection (Hall et al 2020).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In this regard, previous work has shown that macrophage PI3K/AKT signalling is key to a range of cellular processes associated with host-pathogen interaction in MTBC infections, including modulation of cell death pathways, manipulation of signalling downstream of TLRs, and initiation of granuloma formation (Maiti et al 2001;A et al 2012;Cho et al 2013;Liu et al 2016;Brace et al 2017;Yang et al 2018). We have also recently demonstrated that genes encoding protein products embedded in the PI3K/AKT pathway are primary targets for chromatin modifications that substantially alter bAM gene expression in response to M. bovis infection (Hall et al 2020).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, these studies have been expanded to encompass surveys of the bAM epigenome using methylome sequencing and chromatin immunoprecipitation sequencing (ChIP-seq). This work has demonstrated that the transcriptional reprogramming of bAM caused by M. bovis infection is profoundly shaped by chromatin remodelling at gene loci associated with critical components of host-pathogen interaction (O'Doherty et al 2019;Hall et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, these studies have been expanded to encompass surveys of the bAM epigenome using methylome sequencing and chromatin immunoprecipitation sequencing (ChIP-seq). This work has demonstrated that the transcriptional reprogramming of bAM caused by M. bovis infection is profoundly shaped by chromatin remodelling at gene loci associated with critical components of host-pathogen interaction [46,48].…”
Section: Introductionmentioning
confidence: 99%